Systemizing HR Management in Micro-Enterprise– The Case Study of Kak Yus Soya - Mohd Aris, Nurul Fadzilla; Omar, Siti Sarah; Mohd Angsor, Mohd Asmadi (2022)
A micro-enterprise is a type of business entity with the highest proportion of establishments in Malaysia. Between 2015 and 2020, micro-enterprise establishments’ average annual growth rate was 5.4 percent. This consistent growth has drawn attention to the importance of good human resource management (HRM) for the survival and sustainability of micro-enterprises. HRM is widely regarded as unnecessary and costly for micro, small, and medium-sized enterprises (MSME), particularly when the business is family-owned. This case study focused on Kak Yus Soya, a Klang-based soy drink and beancurd microenterprise. Despite being in the industry for ten years, they have yet to advance their business status from micro to small enterprise. They intend to expand their business by focusing on its capitalization of human resources (HR) to build their competitive advantage. However, they are unable to do so due to a lack of HR knowledge and skills. This study aimed to examine the readiness of Kak Yus Soya to integrate HRM into its business activities and develop the most suitable HRM framework based on its needs and capabilities. This case study used a mixed-method strategy that integrated qualitative and quantitative data collection to accomplish the case objectives. At the end of the study, a structured HRM flow for micro-enterprise integrating five HR activities was established for Kak Yus Soya. The activities are: i) assessing employer readiness, ii) HR planning, iii) selection and recruitment, iv) training, and v) performance appraisal.